Richness and Habitat Relationships of Forest Birds in the Zeen Oak Woodland (Forest of Boumezrane, Souk-Ahras), Northeastern Algeria - Menaa, M; Maazi, M.C; Telailia, S; Saheb, M; Boutabia, L; Chafrour, A; Houhamdi, M. (My University, 2016)
Boumezrane's forest is a significant center for biodiversity. Since last year the forest is facing destruction and degradation. Although the forest is recognized as an important area for avian diversity, it has never received ornithological attention. Many studies have been conducted on the relationship of birds with habitat features, however their associations are not completely understood. Hence we need information on the relationship between occurrence of birds and structural components of zeen oak habitats. We examined relative bird abundance by using the point count method and its relationship to environmental descriptors. A total of 68 visits of 39 bird species were recorded in the zeen oak stands. Avian species richness at each point count ranged between four and 14 species. The most dominant families in number of pairs are Paridae (121 pairs), Turdidae (115.5 pairs), Sylviidae (57.5 pairs), Picidae (55.5 pairs), and Fringillidae (43.5 pairs). They cater for more than 70% of the total abundance of the entire community. Using principal component analysis and canonical correspondence analysis methods, we determined that the size of trees with the height of shrub layer is an important criterion for differentiation of the avifauna of Boumezrane. The second criterion is the volume of tree stratum.